KARAKTERISASI TRIKOMA DAN KANDUNGAN GULA TOTAL TEMBAKAU RAJANGAN TEMANGGUNG - Tantri Swandari (Program Studi Agroteknologi INSTIPER, 2018)
Temanggung tobacco is categorized as an aromatic tobacco which cultivated around Mount Sumbing and Sindoro. Many cultivars of Temanggung tobacco planted by farmers and processed as dried sliced leaves. This product is still economically important for farmer and government income. The aim of the research was study character of trichomes and total sugar content of dry sliced Temanggung tobacco. Research materials used are live of dry sliced Temanggung tobacco, ie Pringapus, Sawah, Sindoro, Jambu, dan Lamsi. The measured parameter was the character of trichomes using microscope and Optilab, and also sugar content by Nelson Somogy methods. The result showed that live of dry sliced Temanggung tobacco has variety of color from pale lemon to light brown. Trichome observations shown that the live dry sliced tobacco have varied structure especially in uni-multicelular head. The highest total sugar content was in Sindoro tobacco (15.5%). Keywords: dry-sliced tobacco, trichomes, sugar content, Temanggung